KOMPETENSI ROOM SECTION PADA PRAKTEK KERJA INDUSTRI DI HOTEL OLEH PESERTA DIDIK SMKN 9 BANDUNG - Aprilianti, Lia (2014)
Penelitianiniinginmengungkapkompetensiroom sectionpesertadidik SMK Negeri 9 Bandung dalammelaksanakanPraktekKerjaIndustri di hotel sebagairoom section.Pesertadidikperlumengoptimalkankompetensinyadalammelaksanakantugassebagairoom section.Penelitianinibertujuanuntukmengetahuikompetensi yang dimiliki peseta didikdalammenatatrolleydanperlengkapankamartamu, membersihkandanmerapikankamartamu, sertamembersihkandanmenyimpantrolley.Metodepenelitian yang digunakanadalahmetodedeskriptif.Instrumenpenelitianinimenggunakanteskinerja.Teknikpengambilansampeldalampenelitianinimenggunakansampelpurposive.Hasilpenelitianmenunjukanbahwapesertadidikkompetendalamkompetensimenataperlengkapankamardanmenyusun trolley, pesertadidikkompetendalamkompetensimembersihkandanmerapikankamar, pesertadidiktidakkompetendalamkompetensimerapikandanmenyimpan trolley. Saran hasilpenelitiankompetensiroom sectiondiharapkanpesertadidik yang sedangmelaksanakanPraktekKerjaIndustrisebagairoom section dapatmempersiapkandanmeningkatkankompetensi yang dimilikidengancaraseringberlatihdalammerapikandanmenyimpantrolley This research wants to disclose the room section competency of students of the SMK Negeri 9 Bandung in assigning the Industrial job training in hotel as the room section. The students do necessary optimize their competency in assigning their tasks as room section. It has purpose to examine competencies owned by students in trolley and visitor's room supplies arrangement, clean and make visitor's room neat, and to keep and store the trolley. The research methodology applied in this study is a descriptive method. Meanwhile its instrument applied a performance testing. In this research, the sampling was carried by a purposive sampling method. The research findings show that students are highly competent in arranging the room supplies and compiling trolley, they are also competent in room's cleaning up and making neat; but they are not sufficient competent in keeping and storing trolley in good arrangement. Some recommendations that could be made from research finding is that such room section competency is expected that students are being involved in Industrial Job-Training as room section can prepare and improve their competency by participating as frequently as possible in practicing for keeping neatly and storing the trolley.